The development of healing environment concept: a review - Azi Izwani, Nor Hamzah; Lee, Chia Kuang; Zetty Ain, Kamaruzzaman; Nubli, Abdul Wahab (IOP Publishing, 2020)
Good environment will reflect the user’s life in many aspects. Therefore, many concepts have been developed to produce such good and excellent environment. One of it is healing concept that have a positive effect based on previous research. Although this concept has been developed since many years ago but the understanding and implementation level are still low. Therefore, aim of this study was to explore the development of healing concept consist of several framework and can applied into comprehensive built environment design. Studies started from searching keyword that related with healing garden. The word healing has also substitute with other synonym words that reflect the same meaning. In general, healing can be defined as a good and positive effect of psychology. Finding shows that, healing concept can be applied in the building and landscape design. Healing garden is one of the implementations derive from healing concept. Research suggest for future, is to studies about benefits of healing or restorative concept and focus on specific user. Studies shows that this idea has brighter future to be explore especially for design and built environment specialist. Study contributes to the body of knowledge around practitioner and also researcher